America's new swing region changing politics and demographics in the Mountain West - Teixeira, Ruy A. (Brookings Institution, 2012)
"Analyzes effects of the increase in minorities, younger residents, educational levels, and urbanization on the traditionally Republican politics of six states in the Mountain West, comparing changes in voting patterns from 1988 to 2008. Discusses possible ramifications of those changes and the 2010 mid-term elections on the 2012 presidential election"--Provided by publisher.